Educational Implications That Arise From Differing Models of Human Development and Their Repercussions on Social Innovation - Orón Semper, José Víctor; Akrivou, Kleio; Scalzo, Germán (Frontiers in Education, 2019)
Social innovation aims for creating social value primarily while it recognizes that not all technology-based progress amounts to social progress. We think that this calls for a paradigm shift in how we understand education. No one doubts that education requires intense cognitive effort, but educational proposals certainly vary depending on how cognition is understood. In this article, we suggest that different ways of understanding human development are related to different ways of understanding cognition. Thus, these different conceptions of human development affect their resulting educational proposal. While not an exhaustive account, we sketch out three models of human development, the so-called autonomous self (AS), processual self (PS) and inter-processual self (IPS). Each have different implications for education depending on their particular understanding of cognition. The AS and PS models understand cognition as a primarily rational mastery exercise, with the difference that PS uses relationships and diverse psychological faculties for the subject's cognitive development, whereas AS relies more on the subject's rational agency. On the other hand, IPS understands cognition as a relational act that, when it arises from interiority, affects all dimensions of the person. In the present article, we explore the educational consequences of these different ways of understanding cognition with the assistance of interdisciplinary dialogue from philosophy, psychology and neuroscience, and their repercussion on social innovation with the intention of opening up reflection in the field of education and of inspiring its practitioners to rethink the model they assume. We will conclude with reflections informing educational implications for the design of programs and teacher training itself.